EXPLORING UNIVERSITY STUDENTS’ SELF-REGULATION IN ONLINE FOREIGN LANGUAGE EDUCATION - Gökçe Kurt; Burak Tomak (Istraživanja u Pedagogiji, 2022)
With the spread of the Covid-19 pandemic, online education has been embraced as an instructional delivery mode to ensure continuity in all levels of education including higher education. Given the fact that the success of online learning heavily relies on the learner’s ability to autonomously regulate their learning, this study focuses on self-regulatory behaviors of tertiary level EFL learners enrolled in an online intensive language preparatory program. Quantitative and qualitative data were gathered to explore learners’ perceived levels of online self-regulation; the predictive role of online learning self-efficacy beliefs in their self-regulation; and the strategies they used to regulate their learning in online education. Findings revealed learners’ moderate level of online self-regulation predicted by their self-efficacy beliefs. Moreover, EFL learners used a variety of strategies to regulate their learning before, during and after synchronous online classes.